The efficacy of tart cherry juice in aiding recovery after intermittent exercise - Quinlan, R.; Hill, J. A. (International Journal of Sports Physiology and Performance, 2020)
Purpose: To investigate the effects of supplementation with tart cherry juice (TCJ) on markers of recovery after intermittent exercise under habitual dietary conditions. Methods: Using a randomized, single-blind, placebo (PLA)-controlled, independent-groups design, 20 team-sport players (8 male and 12 female; age 26 [4] y, height 175.4 [9.6] cm, body mass 70.2 [12.6] kg) were divided equally into 2 groups and consumed either TCJ or PLA twice per day for 8 consecutive days while following their normal dietary habits. Participants completed an adapted version of the Loughborough Intermittent Shuttle Test (LIST) on day 6 of supplementation. Countermovement jump, 20-m sprint, maximal voluntary isometric contraction, and delayed onset muscle soreness were assessed at baseline and 1, 24, and 48 hours post-LIST. Blood markers of muscle damage (creatine kinase) and inflammation (C-reactive protein) were taken presupplementation, immediately pre-LIST, and 1, 24, and 48 hours post-LIST. Data were analyzed using a repeated-measures analysis of variance. Results: Countermovement jump, 20-m sprint, and maximal voluntary isometric contraction showed significantly faster recovery with TCJ (P<.05) at 24 and 48 hours post-LIST. A significant interaction effect (P<.05) was observed for muscle soreness; however, Bonferroni post hoc analysis could not identify when the significant differences between TCJ and PLA occurred. There were no significant differences throughout recovery between TCJ and PLA for C-reactive protein and creatine kinase (P<.05). Conclusion: The results suggest that TCJ, in addition to habitual diet, can accelerate recovery after intermittent exercise and therefore extend the efficacy of TCJ in accelerating recovery in team sports.